Changes in the content of pollen total lipid and TAG in Arabidopsis thaliana DGAT1 mutant as11. Issue 2 (22nd March 2023) - Bai, Mei; Gao, Han; Yang, Yang; Wu, Hong
Abstract: In mature pollen grains, lipids are primarily stored in the form of lipid droplets that provide energy and act as a carbon source for normal pollen development and germination. Triacylglycerol (TAG) is the major form of stored plant lipids. Diacylglycerol transferase, which is encoded by DGAT1 in Arabidopsis thaliana, is an important enzyme regulating triacylglycerol synthesis. Within the seeds of the DGAT1 mutant as11, the content of TAG is significantly decreased and the fatty acid composition also differs from the wild type. Transcriptome data of mature anthers showed that the genes involved in the TAG synthesis pathway were downregulated in as11 . Analysis of gene expression patterns via transcriptome data also revealed that the expression of PDAT1, which functions in a manner complementary to the DGAT1 gene, was significantly decreased in as11, whereas the amylopectin synthase genes SS1 and SS2 were upregulated in mutant as11 . We also detected lower total lipid, TAG and fatty acid contents in mature as11 pollen, with palmitic acid (C16:0) and linolenic acid (C18:3) being the major fatty acids in mature pollen. The cytological results showed that the lipid droplet content was reduced in mature as11 pollen. In the binuclear pollen grain II stage, WT pollen contained lipid droplets that were primarily accumulated around the generative nucleus, whereas the pollen in the mutant as11 was rich in starch grains that were primarily distributed around the vegetative nucleus. Ultrastructural analysis indicated that during pollen development in as11, the amount of endoplasmic reticulum in tapetal cells and pollen grains decreased, whereas the Golgi body content increased, which directly or indirectly led to a decrease in the levels of lipidosomes and an increase in the starch content in as11 . Changes in the lipid content and fatty acid composition of the mutant as11 differ from those in the wild type during pollen development. Abstract : Diacylglycerol transferase, which is encoded by DGAT1 in Arabidopsis thaliana, is an important enzyme that regulates triacylglycerol synthesis. Transcriptome data of mature anthers showed that the genes involved in the TAG synthesis pathway were downregulated in DGAT1 mutant as11. The total lipid, TAG and fatty acid contents were reduced in as11 mature pollen, with palmitic acid (C16:0) and linolenic acid (C18:3) being the major fatty acids in mature pollen. The cytological results showed that the lipid droplet content was lower in mature as11 pollen compared to the wild type.